1986
DOI: 10.1037/0735-7044.100.5.745
|View full text |Cite
|
Sign up to set email alerts
|

Retention and acquisition of classical trace conditioned responses by rabbits with hippocampal lesions.

Abstract: The effects of dorsal hippocampal lesions on retention of classical trace conditioned responses were examined using the rabbit nictitating membrane preparation. Animals were trained to criteria and then lesioned either in the cortex or in the hippocampus and the cortex. Hippocampal damage had no effect on the retention of responses but produced significantly longer onset latencies. A control group of hippocampal animals acquired conditioned responses (CRs) at least as quickly as the prelesion subjects, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
113
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 33 publications
11
113
1
Order By: Relevance
“…the lesioned subject experiences the delay to the large reinforcer as longer than it actually is, causing it to value the reinforcer less than shams). The evidence for the role of the H in temporal perception is inconclusive: some studies have found that aspirative hippocampal lesions did not affect timing behaviour (Dietrich & Allen, 1998;Dietrich, Allen, & Bunnell, 1997;Port, Romano, Steinmetz, Mikhail, & Patterson, 1986;Rawlins, Winocur, & Gray, 1983), whereas others have suggested that lesions of the hippocampus or fimbria/fornix speed up an internal clock, or reduce the estimation of time periods when a stimulus being timed is interrupted (Hata & Okaichi, 1998;Meck, 1988;Meck, Church, & Olton, 1984;Olton, Meck, & Church, 1987;Wallenstein, Eichenbaum, & Hasselmo, 1998). In any case, H-lesioned rats were better at learning with delayed reinforcement but worse at choosing it, suggesting that self-controlled choice and learning with delayed reinforcement tax different psychological processes.…”
Section: Hippocampus (H)mentioning
confidence: 99%
“…the lesioned subject experiences the delay to the large reinforcer as longer than it actually is, causing it to value the reinforcer less than shams). The evidence for the role of the H in temporal perception is inconclusive: some studies have found that aspirative hippocampal lesions did not affect timing behaviour (Dietrich & Allen, 1998;Dietrich, Allen, & Bunnell, 1997;Port, Romano, Steinmetz, Mikhail, & Patterson, 1986;Rawlins, Winocur, & Gray, 1983), whereas others have suggested that lesions of the hippocampus or fimbria/fornix speed up an internal clock, or reduce the estimation of time periods when a stimulus being timed is interrupted (Hata & Okaichi, 1998;Meck, 1988;Meck, Church, & Olton, 1984;Olton, Meck, & Church, 1987;Wallenstein, Eichenbaum, & Hasselmo, 1998). In any case, H-lesioned rats were better at learning with delayed reinforcement but worse at choosing it, suggesting that self-controlled choice and learning with delayed reinforcement tax different psychological processes.…”
Section: Hippocampus (H)mentioning
confidence: 99%
“…However, neurons in hippocampus display activation profiles that match the topography of the CR in the NMR conditioning task (Berger eta!., 1976;Berger & Thompson, 1978;Clark et al, 1984;Solomon eta!., 1986). In addition, hippocampal lesions can sometimes disrupt timing of the CR in trace conditioning (Port et al, 1986a;Solomon et al, 1986) and more complicated paradigms (Orr & Berger, 1985;Port eta!., 1986b). This experimental data has implicated the hippocampus in the timing of the NMR.…”
Section: The Hippocampus and Spectral Timingmentioning
confidence: 99%
“…For instance, several investigators have suggested that the hippocampus performs a temporal processing that is utilized by the cerebellum (see e.g., Port et al 1986;Christiansen and Schmajuk 1992). It is therefore of interest to determine to what extent conditioning, which uses direct stimulation of the mossy fiber input to the cerebellum as the CS, resembles conditioning to a peripheral CS.…”
Section: Introductionmentioning
confidence: 99%